Impact of Telemedicine on Hospitalisation and Mortality Rates in Community Based Haemodialysis Centres in Singapore during the COVID-19 Pandemic - Wong, Weng Kin (Academy of Medicine Singapore, 2021)
10.47102/annals-acadmedsg.2020369